Biorisk associated with faecal and airborne antibiotic resistant pathogenic bacteria from swiftlet houses - Sui Sien, Leong (2015)
Determination and identification of 1000 faecal and 200 airborne bacteria isolates of swiftlet (Aerodramus species) were carried out using conventional biochemical tests, genotypic characterization by (GTG)5- PCR and 16S rRNA gene sequencing. PCR were applied in the molecular detection of various pathogenic genes in Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis and Bacillus cereus. These were the first of such studies undertaken in Sarawak. Data obtained were analysed using paired t-test, two-way ANOVA, multiple and logistic regression. The highest mean bacterial colony count (11.86±3.11 log10 cfu/g) in the faecal samples collected from Kota Samarahan and the lowest (6.71±1.09 log10 cfu/g) from Sibu. The highest mean total airborne bacteria colony count (3.08±0.29 log10 cfu/m2/sec) was found in Miri and the lowest (1.05±0.85 log10 cfu/m2/sec) in Sibu. A total of 1200 bacterial isolates were identified by phenotypic and genotypic characterization with 97.5% (faecal bacteria) and 93.5% (airborne bacteria) predominantly were Gram positive bacteria. Staphylococcus sp. and Bacillus sp. were isolated with the highest prevalence. MAR index for Gram positive bacteria was significantly higher (P<0.05) than that of Gram negative bacteria. The pathogenic faecal and airborne bacteria showed moderate to high level of resistance to penicillin and cephalosporin antibiotic groups.